DYNAMIC INFLUENCE CAUSED BY CLOSE BLASTING ON PRIMARY AND SECONDARY SUPPORT SYSTEM IN TUNNEL "SV. ROK" - Zvonimir Ester; Mario Dobrilović; Darko Vrkljan (Rudarsko-geološko-naftni Zbornik, 2003)
At the construction site of the road tunnel Sv. Rok, the second, left tunnels tube is being constructed parallel to the unfinished right tunnel. The part of right tunnel tube is supported with primary support system according to NAMT, the second part is supported complete with concrete. Distance between axes of the tunnel tubes is approximately 35 m. Drifting of the left tube is being done by blasting. A potential problem of damaging the surrounding rock and support system was recognized. It is well known that the ground vibration particle velocity due to a blast is a measure of damage on the nearby construction. The three component seismographs were used to measure ground oscillation velocities in the right tunnel tube. Total of 30 measurements were executed and 720 values were processed (including all three component oscillation velocities). Maximum ground oscillation velocity recorded was 232.061 mm/s. This paper brings conclusion derived from monitoring data achieved at close proximity to the blasting area, damage level criteria for the rock mass and support system and discusses how these results could assist further development in the control of blasting technique.